Propylthiouracil Induced Pulmonary-Renal Syndrome: a Case Report. - Boattini, M (2015)
Propylthiouracil (PTU) is known to induce antineutrophil cytoplasmatic antibody (ANCA) seropositivity; however, small vessel vasculitis (SVV) with pulmonary and renal involvement is rare. We present the case of an 81-year-old woman on PTU treatment due to toxic nodular goitre who developed alveolar hemorrhage and rapidly progressive glomerulonephritis. The authors highlight the importance of early recognising drug-induced pulmonary-renal syndrome (PRS) in order to avoid unnecessary tests, a delay in the diagnosis and evolution to end-stage kidney disease or life-threatening conditions.